(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This paper presents computational results of incompressible steady flows simulations by solving the Navier-Stokes equations using a finite element method combined with the characteristic based split scheme (CBS). The classical finite element method called Bubnov-Galerkin or Galerkin Method (FEM) is considered the best method for solving purely diffusion problems, however, in case of problems with convection dominant as in many problems of fluid flows, the FEM produces oscillating solutions for high Reynolds numbers. The main goal of this work is to highlight the simulation method and the results of some common tridimensional problems used for code validation and verification. The results show great agreement with literature.